Revealing Global Influences on Organizational Behavior: Mengungkap Pengaruh Global pada Perilaku Organisasi - Julianto, Julianto; Sari, Herlinda Maya Kumala (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of work motivation, career development, and work environment on Organizational Citizenship Behavior (OCB) among employees of PT Coca Cola Europacific Partners Indonesia Pasuruan Plant. Using a quantitative approach with 60 respondents selected through saturated sampling, data analysis was conducted using SPSS version 24. The results indicate that work motivation and work environment significantly influence OCB, while career development has a positive but non-significant effect. Additionally, the combined effect of these factors significantly influences OCB. These findings underscore the importance of fostering a supportive work environment and promoting work motivation to enhance OCB, while also emphasizing the need for providing adequate career development opportunities. Understanding these factors can aid in developing strategies to promote a positive organizational culture and improve overall organizational performance. Hightlight: Work motivation and environment influence OCB significantly. Career development positively affects OCB but not significantly. Understanding OCB factors enhances organizational performance. Keywords: Work Motivation, Career Development, Work Environment, Organizational Citizenship Behavior (OCB), PT Coca Cola Europacific Partners Indonesia.